No effect of whole-hand water flow stimulation on skill acquisition and retention during sensorimotor adaptation - Le Cong, Dat; Sato, Daisuke; Ikarashi, Koyuki; Ochi, Genta; Fujimoto, Tomomi; Yamashiro, Koya (Frontiers in Human Neuroscience, 2024)
Introduction: Repetitive somatosensory stimulation (RSS) is a conventional approach to modulate the neural states of both the primary somatosensory cortex (S1) and the primary motor cortex (M1). However, the impact of RSS on skill acquisition and retention in sensorimotor adaptation remains debated. This study aimed to investigate whether whole-hand water flow (WF), a unique RSS-induced M1 disinhibition, influences sensorimotor adaptation by examining the hypothesis that whole-hand WF leads to M1 disinhibition; thereby, enhancing motor memory retention. Methods: Sixty-eight young healthy participants were randomly allocated to three groups based on the preconditioning received before motor learning: control, whole-hand water immersion (WI), and whole-hand WF. The experimental protocol for all the participants spanned two consecutive days. On the initial day (day 1), baseline transcranial magnetic stimulation (TMS) assessments (T0) were executed before any preconditioning. Subsequently, each group underwent their respective 30-min preconditioning protocol. To ascertain the influence of each preconditioning on the excitability of the M1, subsequent TMS assessments were conducted (T1). Following this, all participants engaged in the motor learning (ML) of a visuomotor tracking task, wherein they were instructed to align a cursor with a target trajectory by modulating the pinch force. Upon completion of the ML session, final TMS assessments (T2) were conducted. All participants were required to perform the same motor learning 24 h later on day 2. Results: The results revealed that whole-hand WF did not significantly influence skill acquisition during sensorimotor adaptation, although it did reduce intracortical inhibition. This phenomenon is consistent with the idea that S1, rather than M1, is involved in skill acquisition during the early stages of sensorimotor adaptation. Moreover, memory retention 24 h after skill acquisition did not differ significantly across the three groups, challenging our initial hypothesis that whole-hand WF enhances memory retention throughout sensorimotor adaptation. This could be due to the inability of whole-hand WF to alter sensorimotor connectivity and integration, as well as the nature of the plastic response elicited by the preconditioning. Discussion: In conclusion, these findings suggest that although whole-hand WF attenuates intracortical inhibition, it does not modulate skill acquisition or motor memory retention during sensorimotor adaptation.